Subcellular localization of an intracellular serine protease of 68 kDa in Leishmania (Leishmania) amazonensis promastigotes - José Andrés Morgado-Díaz; Raquel Elisa da Silva-Lopez; Carlos Roberto Alves; Maurilio José Soares; Suzana Corte-Real; Salvatore Giovanni De Simone (Memorias do Instituto Oswaldo Cruz, 2005)
Here we report the subcellular localization of an intracellular serine protease of 68 kDa in axenic promastigotes of Leishmania (Leishmania) amazonensis, using subcellular fractionation, enzymatic assays, immunoblotting, and immunocytochemistry. All fractions were evaluated by transmission electron microscopy and the serine protease activity was measured during the cell fractionation procedure using a-N-r-tosyl-L-arginine methyl ester (L-TAME) as substrate, phenylmethylsulphone fluoride (PMSF) and L-1-tosylamino-2-phenylethylchloromethylketone (TPCK) as specific inhibitors. The enzymatic activity was detected mainly in a membranous vesicular fraction (6.5-fold enrichment relative to the whole homogenate), but also in a crude plasma membrane fraction (2.0-fold). Analysis by SDS-PAGE gelatin under reducing conditions demonstrated that the major proteolytic activity was found in a 68 kDa protein in all fractions studied. A protein with identical molecular weight was also recognized in immunoblots by a polyclonal antibody against serine protease (anti-SP), with higher immunoreactivity in the vesicular fraction. Electron microscopic immunolocalization using the same polyclonal antibody showed the enzyme present at the cell surface, as well as in cytoplasmic membranous compartments of the parasite. Our findings indicate that the internal location of this serine protease in L. amazonensis is mainly restricted to the membranes of intracellular compartments resembling endocytic/exocytic elements.